2001
DOI: 10.1677/joe.0.170r001
|View full text |Cite
|
Sign up to set email alerts
|

Chronic food-restriction alters the expression of somatostatin and growth hormone-releasing hormone in the ovariectomised ewe

Abstract: Changes in the secretion of GH induced by long-term alterations in nutritional status are thought to result from alterations in somatostatin (SRIF) and growth hormonereleasing hormone (GHRH) at the level of the hypothalamus. To date however, the effect of nutrition on the gene expression of SRIF and GHRH in a species where GH secretion is increased by food restriction, as is the case for the sheep and human, remains unknown. We determined the effect of under-nutrition on the expression of SRIF and GHRH in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
34
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 38 publications
(44 reference statements)
10
34
0
Order By: Relevance
“…Fasting has been shown to suppress HPT SST mRNA in male mice and ewes (21,29,46), consistent with the current observations showing an overall reduction in HPT SST mRNA, which reached significance in females (Fig. 3A).…”
Section: Resultssupporting
confidence: 92%
“…Fasting has been shown to suppress HPT SST mRNA in male mice and ewes (21,29,46), consistent with the current observations showing an overall reduction in HPT SST mRNA, which reached significance in females (Fig. 3A).…”
Section: Resultssupporting
confidence: 92%
“…The fat ewes in our study had substantially higher circulating concentrations of leptin than the lean ewes and this is consistent with our previous studies using this model of dietary manipulation [45, 63]. It is well accepted that leptin is synthesized in adipocytes and inhibits appetite and plays a role in regulating energy expenditure [64, 65].…”
Section: Discussionsupporting
confidence: 91%
“…Taken together, these results suggest that there are both positive and negative regulators of GHRH expression in the fasted state, where under certain physiologic conditions the balance between these regulators can be skewed to favor GHRH synthesis. This logic is supported by the report of Henry et al (2001), who observed that food restriction in the ovariectomized ewe, which increases NPY mRNA (McShane et al 1993), also increased GHRH mRNA.…”
Section: Seungjoon Park and Others · Effects Of Fasting On The Gh-axisupporting
confidence: 62%